2022
DOI: 10.1177/11795549221109493
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LIMA1 Indicates Poor Prognosis and Promotes Epithelial-Mesenchymal Transition in Head and Neck Squamous Cell Carcinoma

Abstract: Background: LIMA1 encodes LIM domain and actin binding 1, a cytoskeleton-associated protein whose loss has been linked to migration and invasion behavior of cancer cells. However, the roles of LIMA1 underlying the malignant behavior of tumors in head and neck squamous cell carcinoma (HNSC) are not fully understood. Methods: We conducted a multi-omics study on the role of LIMA1 in HNSC based on The Cancer Genome Atlas data. Subsequent in vitro experiments were performed to validate the results of bioinformatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…Similarly, LIMA1 depletion was found to promote EMT and induced actin cytoskeleton remodeling in breast cancers (43) and epithelial ovarian cancers (44) significantly enhancing the migration and invasion of epithelial cancer cells both in vivo and in vitro. And another study found that the expression of LIMA1 was upregulated in head and neck tumors, driving invasion and metastasis by activating tumor-associated pathways such as PI3K-AKT and JAK-STAT signaling pathways to promote the EMT process (45). It is considered likely that DNA demethylation of the LIMA1 promoter region results in different expression levels of LIMA1 in HNSC.…”
Section: Dynamic Maintenance Of the Epithelial Mesenchymal Transitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, LIMA1 depletion was found to promote EMT and induced actin cytoskeleton remodeling in breast cancers (43) and epithelial ovarian cancers (44) significantly enhancing the migration and invasion of epithelial cancer cells both in vivo and in vitro. And another study found that the expression of LIMA1 was upregulated in head and neck tumors, driving invasion and metastasis by activating tumor-associated pathways such as PI3K-AKT and JAK-STAT signaling pathways to promote the EMT process (45). It is considered likely that DNA demethylation of the LIMA1 promoter region results in different expression levels of LIMA1 in HNSC.…”
Section: Dynamic Maintenance Of the Epithelial Mesenchymal Transitionmentioning
confidence: 99%
“…Recent studies have shown that the LIMA1 gene exhibits frequent downregulation and loss in cancers (Figure 3), and it can be involved in the development of malignancy through various mechanisms (13) (Figure 4). LIMA1 is associated with the progression and metastasis of various solid tumors including oral cancer (8), esophageal cancer (79), gastric cancer (80), prostate cancer (11, 41, 42, 81), breast cancer (43), ovarian cancer (44), and head and neck squamous cell carcinoma (45,46), as well as osteosarcoma (82) and lymphoma (83, 84) (Table 2). Moreover, LIMA1 particularly plays a crucial role in biological processes such as tumor proliferation, apoptosis, migration, invasion, drug resistance, immune response (79,80).…”
Section: Roles Of Lima1 In Cancer Development and Progressionmentioning
confidence: 99%
See 3 more Smart Citations